The Relationship between Family Communication and Self-Management - Rahmat Kartolo; Sutarini; Dalmi Iskandar; Ahmad Dwi Rifai (International Journal of Educational Research Excellence (IJERE), 2023)
This research is research that aims to determine the relationship between family communication and student self-management in class IX of SMP Negeri 25 Medan. The sample in this study was 40 students in class IX of SMP Negeri 25 Medan. The instrument used by researchers was a questionnaire to collect family communication and self-management data which was previously tested to determine the validity and reliability of the questionnaire. Of the 30 questionnaire items distributed, there were 28 valid questionnaire items and 2 invalid items. The correlation test technique uses the product moment correlation formula. From the calculation results, the correlation coefficient between family management (x) and self-management (Y) is 0.498. According to the interpretation of the product moment correlation index, this figure shows a strong or high relationship. The hypothesis testing technique used is the t test formula. The results of the hypothesis test stated that there was a significant relationship between family communication and self-management in class IX students of SMP Negeri 25 Medan, at a significance level of 5% (t count > t table: 7.655 > 0.361). Researchers suggest that guidance and counseling teachers should be more varied and tailored to students' needs and the goals they want to achieve so that they can influence family communication on the success of students' self-management.